2014
DOI: 10.1016/j.ccr.2014.04.005
|View full text |Cite|
|
Sign up to set email alerts
|

Depletion of Carcinoma-Associated Fibroblasts and Fibrosis Induces Immunosuppression and Accelerates Pancreas Cancer with Reduced Survival

Abstract: Summary Pancreatic ductal adenocarcinoma (PDAC) is associated with marked fibrosis and stromal myofibroblasts but their functional contribution remains unknown. Transgenic mice with ability to delete αSMA+ myofibroblasts in pancreatic cancer were generated. Depletion starting at either non-invasive precursor (PanIN) or the PDAC stage led to invasive, undifferentiated tumors with enhanced hypoxia, epithelial-to-mesenchymal transition and cancer stem cells, with diminished animal survival. In PDAC patients, lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,901
15
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,020 publications
(2,042 citation statements)
references
References 51 publications
61
1,901
15
8
Order By: Relevance
“…Nevertheless, at this stage more basic knowledge regarding targeting of PSCs and desmoplasia is needed. Recent publication in PDAC research question whether inhibition of stroma and fibrosis is advantageous as, on one hand, it may improve the drug delivery but, on the other hand, it may remove restrain on tumour growth and metastasis 45, 46, 47…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, at this stage more basic knowledge regarding targeting of PSCs and desmoplasia is needed. Recent publication in PDAC research question whether inhibition of stroma and fibrosis is advantageous as, on one hand, it may improve the drug delivery but, on the other hand, it may remove restrain on tumour growth and metastasis 45, 46, 47…”
Section: Discussionmentioning
confidence: 99%
“…Our work points toward a detrimental role of PSCs by promoting immunosuppression while another new study suggests that the presence of PSCs-related fibrosis could prevents the recruitment of Tregs into PDAC. 10 Now, further basic and clinical investigations are needed to clarify the PSCs-immune system interplay in pancreatic cancer in order to find the right multi-targeting strategy for improving current treatment.…”
Section: Ip-10/cxcl10 Attracts Regulatory T Cellsmentioning
confidence: 99%
“…32 Similar reports came from another study in which authors demonstrated that depleting myofibroblasts correlated with reduced survival, tumor undifferentiating, invasion and increased epithelial-to-mesenchymal transition. 33 Therefore, both studies underscore the need for caution in targeting carcinoma-associated fibroblasts. Depletion of myeloid cells, by pharmacological approaches, was instead efficient in increasing intratumoral accumulation of activated CD8…”
Section: Gr1mentioning
confidence: 99%